MECHANISM FOR FISCAL STIMULATION OF THE DEVELOPMENT OF THE DIGITAL ECONOMY: ESSENCE AND FEATURES OF FUNCTIONING - Yakushko , I.V. (The actual problems of regional economy development, 2023)
The development of the digital economy, which is happening all over the world today, proves that there is no alternative to the process of further digital transformation of economic relations, which actualizes the issue of activating such a transformation of the national economy. The purpose of the article is to deepen the theoretical foundations of the use of fiscal tools for the development of the digital economy through the substantiation of the conceptual foundations of the formation and functioning of the mechanism of such stimulation. To achieve this goal, the article uses a set of general and special methods of scientific research, namely: comparison, systematic approach, method of content analysis, abstraction, analysis and synthesis, and graphic visualization. The article examines the theoretical and methodological provisions of the functioning of the mentioned mechanism as an integral and objectively necessary component of the general system of state regulation of economic relations in the field of digitalization of the national economy. In particular, the content of such concepts as “fiscal stimulation”, “tax stimulation” was studied. Accordingly, it is determined that fiscal stimulation is a process of influencing the activities of economic entities through the use of fiscal instruments, i.e, a set of means used to accumulate financial resources of economic entities to generate state budget revenues. Taking into account the obtained results, the essence of the specified mechanism was specified, and it was proposed to consider it as a set of measures, methods, principles and concepts, which collectively determine the peculiarities of the application of fiscal instruments for the development of economic relations based on the use of modern information and communication technologies in the production, distribution, exchange and consumption. Also, in the process of conducting a scientific study, great attention was paid to the identification of the basic components of such mechanism and the display of their interrelations. At the same time, the principles of the specified mechanism are considered in detail, which include the following: principles of formation (scientific, historicity, resource provision, systematicity, rationality, duration) and the principles of development (harmony, effectiveness, adaptability, efficiency). The last group was expanded by two new principles: consumerism and transparency. In the article, their essence is revealed, and the implementation of these principles are substantiated, their observance in the future will increase the effectiveness of the mechanism of fiscal stimulation of the national economy development.